2000
DOI: 10.1126/science.290.5498.1959
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulin Release from Genetically Engineered K Cells

Abstract: Genetic engineering of non-beta cells to release insulin upon feeding could be a therapeutic modality for patients with diabetes. A tumor-derived K-cell line was induced to produce human insulin by providing the cells with the human insulin gene linked to the 5'-regulatory region of the gene encoding glucose-dependent insulinotropic polypeptide (GIP). Mice expressing this transgene produced human insulin specifically in gut K cells. This insulin protected the mice from developing diabetes and maintained glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
168
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(177 citation statements)
references
References 20 publications
3
168
1
4
Order By: Relevance
“…Preproinsulin biosynthesis has been achieved in a variety of endocrine cells like K-cells (48) or cells from pituary (49)(50)(51), exocrine pancreas (52), and submandibular glands (42), as well as in nonendocrine cells like muscle cells (53,54), and fibroblasts (55). However, in some of the endocrine cell lines (e.g.…”
Section: Engineering Of a Surrogate β-Cellmentioning
confidence: 99%
“…Preproinsulin biosynthesis has been achieved in a variety of endocrine cells like K-cells (48) or cells from pituary (49)(50)(51), exocrine pancreas (52), and submandibular glands (42), as well as in nonendocrine cells like muscle cells (53,54), and fibroblasts (55). However, in some of the endocrine cell lines (e.g.…”
Section: Engineering Of a Surrogate β-Cellmentioning
confidence: 99%
“…In that study, they found that mice expressing this transgene produced human insulin specifically in gut K cells. This insulin protected the mice from developing diabetes and maintained glucose tolerance after the destruction of the native insulin-producing beta cells [6].…”
mentioning
confidence: 94%
“…For their purpose, they selected gut K cells that have been shown to express glucokinase, the glucose sensor of pancreatic beta cells. Transgenic mice expressing human insulin under the control of a K cell-specific promoter were shown to be resistant to T1DM development induced by the beta cell toxin streptozotocin in an earlier study [6]. K cells release glucose-dependent insulinotropic polypeptide (GIP), a gastrointestinal hormone that is secreted in response to food intake and that modulates beta cell function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pluripotent adult or embryonic stem cells that can be differentiated into insulin-producing cells have therefore attracted much attention. Cells isolated from pancreatic ducts or from the gastrointestinal tract could be differentiated or genetically manipulated to produce insulin [3,4,5] and were capable of reversing insulin-dependent diabetes in mice [3,5]. Similarly, mouse embryonic stem (ES) cells secreting insulin were selected using a gene-trap strategy in vitro and could normalize glycaemia in diabetic mice, but this effect was only transient in 40% of the mice [6].…”
mentioning
confidence: 99%